(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the procedures for proper response and prevention in technogenic emergency situations. Technogenic emergencies, arising from industrial accidents, technological failures, and human-induced hazards, pose serious threats to human life, infrastructure, and the environment. The study highlights the importance of preparedness, early warning systems, coordinated response mechanisms, and preventive measures aimed at minimizing risks and consequences. Special attention is given to the role of institutions, emergency services, and public awareness in ensuring effective management of technogenic emergencies.